Cloning, characterization, and effects of overexpression of the Escherichia coli rnd gene encoding RNase D. - Zhang, J R (1988)
RNase D is a 3'-exoribonuclease whose in vitro specificity has suggested that it is involved in the processing of tRNA precursors. Its in vivo role has remained unclear, however, because mutant cells devoid of the enzyme display no defect in growth or tRNA processing. To learn more about the structure and function of RNase D, we cloned the Escherichia coli rnd gene, which is thought to code for this enzyme. The rnd gene was isolated from a cosmid library based on elevated RNase D activity and was subcloned as a 1.4-kilobase-pair fragment in pUC18. Maxicell analysis of the cloned fragment revealed that a single protein of approximately 40 kilodaltons, which is the size of RNase D, was synthesized. The rnd gene is present as a single copy on the E. coli chromosome and is totally absent in a deletion mutant. Cells that harbored the cloned rnd gene displayed RNase D activity that was elevated as much as 20-fold over that of the wild type. As growth of the culture progressed, however, RNase D specific activity declined dramatically, together with a similar decrease in plasmid copy number. In contrast, no decrease in copy number was observed with an inactive rnd gene. Placement of the rnd gene downstream from the lac promoter led to inducible RNase D overexpression and concomitantly slowed cell growth. These findings support the idea that rnd is the structural gene for RNase D and indicate that elevated RNase D activity is deleterious to E. coli.